No Difference in Complications Between Elbow Ulnar Collateral Ligament Reconstruction With the Docking and Modified Jobe Techniques: A Systematic Review and Meta-analysis. Issue 8 (July 2022) - Looney, Austin M.; Fackler, Nathan P.; Pianka, Mark A.; Bodendorfer, Blake M.; Fryar, Caroline M.; Conroy, Christine M.; Israel, Jacob E.; Wang, David X.; Ciccotti, Michael G.; Chang, Edward S.
Background: The most commonly used techniques for elbow ulnar collateral ligament reconstruction (UCLR) are the docking and modified Jobe figure-of-8 techniques. Previous literature has suggested that UCLR with the docking technique is associated with fewer complications; however, these studies included results from the original classic Jobe technique without controlling for the effects of flexor pronator mass (FPM) detachment and routine submuscular ulnar nerve transposition (UNT). Purpose/Hypothesis: This study sought to compare the rates of complications and subsequent unplanned surgical procedures between the docking and figure-of-8 techniques. We hypothesized that there would be no significant difference in the rates of complications or subsequent unplanned surgical procedures between the techniques when the FPM was preserved and no routine submuscular UNT was performed. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: This study was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A series of mixed-effects multivariate metaregression models were implemented using the restricted maximum likelihood method. Complications and subsequent unplanned surgical procedures were modeled as Freeman-Tukey transformed incidence rates for variance stabilization, and nerve-specific complications were assessed as the Freeman-Tukey transformed proportion of cases, with back-transformation to estimate summary effects. Results: There were 19 studies eligible for qualitative analysis, consisting of 1788 cases of UCLR (303 docking, 1485 figure-of-8), 18 of which were suitable for quantitative analysis (1769 cases; 291 docking, 1478 figure-of-8). A total of 338 complications were reported (17 for docking, 321 for figure-of-8), the majority of which were nerve related. Additionally, a total of 75 subsequent unplanned surgical procedures were related to the index UCLR procedure. There was no significant difference in the rate of complications ( P = .146) or proportion of cases with nerve-specific complications ( P = .127) between the docking and figure-of-8 techniques when controlling for FPM preservation versus detachment with submuscular UNT. FPM detachment with submuscular UNT was independently associated with a significantly higher proportion of postoperative nerve-related complications ( P = .004). There was also no significant difference in the rates of subsequent unplanned surgical procedures between the docking and figure-of-8 techniques ( P = .961), although FPM detachment with routine submuscular UNT was independently associated with a significantly higher incidence of subsequent unplanned surgical procedures. Conclusion: The results of this study demonstrate no significant difference in the rates of complications or subsequent unplanned surgical procedures between the figure-of-8 and docking techniques for UCLR when controlling for FPM preservation versus detachment with submuscular UNT. With modern muscle-sparing approaches and avoiding submuscular UNT, the modified Jobe technique does not differ significantly from the docking technique in terms of complication rates, proportions of cases with nerve-specific complications, or rates of subsequent unplanned surgical procedures.